1996
DOI: 10.1074/jbc.271.14.8034
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion Toxins Affecting Sodium Current Inactivation Bind to Distinct Homologous Receptor Sites on Rat Brain and Insect Sodium Channels

Abstract: Sodium channels posses receptor sites for many neurotoxins, of which several groups were shown to inhibit sodium current inactivation. Receptor sites that bind ␣-and ␣-like scorpion toxins are of particular interest since neurotoxin binding at these extracellular regions can affect the inactivation process at intramembranal segments of the channel. We examined, for the first time, the interaction of different scorpion neurotoxins, all affecting sodium current inactivation and toxic to mammals, with ␣-scorpion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
259
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 187 publications
(268 citation statements)
references
References 62 publications
9
259
0
Order By: Relevance
“…Some anemones also contain smaller peptide toxins that selectively block specific potassium channels. Most anemones also contain potent cytolytic proteins called actinoporins, which permeabilize cell membranes and ultimately cause cell death (6,9). The use of toxins and venoms as the basis of natural products can provide new biomedical research tools and unique molecular models for designing anticancer drugs (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Some anemones also contain smaller peptide toxins that selectively block specific potassium channels. Most anemones also contain potent cytolytic proteins called actinoporins, which permeabilize cell membranes and ultimately cause cell death (6,9). The use of toxins and venoms as the basis of natural products can provide new biomedical research tools and unique molecular models for designing anticancer drugs (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Scorpion α-like toxins belong to the same group but distinguish themselves by acting on both mammals and insects. However, they do not bind to rat brain synaptosomes (Gordon et al, 1996;Gordon, 1998;Possani et al, 1999). The nomenclature of these α-like toxins is primarily based on the results of binding displacement studies, while the properties of α-and α-like toxins from an electrophysiological point of view are in fact alike (Couraud et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…5). Several studies have demonstrated the functionally relevant structural differences in insect and mammalian receptor site 3 regions (Gordon et al, 1996). Although more structure-function work is necessary to completely unravel these structural differences, these phyla depending differences do support the arguments to target site 3 in the search for new Na V channel acting insecticides (Cohen et al, 2006).…”
Section: Insect-selective Gating Modifiers Of Inactivation: Site-3 Tomentioning
confidence: 97%
“…Another toxin from the same sea anemone, ATX-II is toxic to both insect and mammalian Na V channels. However, its binding affinity for cockroach neuronal membranes is very high whereas its binding affinity for rat brain synaptosomes is low (Gordon et al, 1996). Furthermore, ATX-II binds with extreme high potency to site 3 of insect Na V channels, resulting in a strong slowing down of the fast inactivation (Warmke et al, 1997).…”
Section: Site 3 Toxins From Sea Anemone Venommentioning
confidence: 99%